THE EFFECTIVENESS OF PROBLEM-BASED LEARNING METHOD IN THE IMPLEMENTATION OF 2013 CURRICULUM AT VOCATIONAL HIGH SCHOOL - Widya Astriyanda; M. Raihan Afrizal; Margaret Stevani (Smart Education, 2023)
This study aimed to describe the initial conditions of learning in the application of the 2013 Curriculum and learning conditions after implementing problem-based learning. This research was part of the development of a problem-based learning model in implementing the 2013 curriculum. The sample in this study was 19 teachers who applied problem-based learning in implementing the 2013 curriculum at Vocational High School I Nur Hasanah, North Sumatra. Data was collected using a questionnaire technique through focused group discussion. Data analysis was carried out descriptively. The results of the first year's research showed that: (1) Problem-based learning had the potential to be applied in the implementation of the 2013 Curriculum in Vocational High Schools. Teacher readiness in implementing the 2013 Curriculum was included in the high category with an average price of 96.73 and an achievement score of 82%. The suitability of learning implementation in the application of the 2013 Curriculum was included in the high category with an average of 152.26 and an achievement score of 78%. Most of the teachers stated that problem-based learning was appropriate to be applied in every subject in the implementation of the 2013 Curriculum; (2) Problem-based learning was proven to be able to increase student competency in terms of abilities and attitudes.